IoT Framework Current Trends and Recent Advances to Management Company in The PT.TNC - Teddy Surya Gunawan; B Herawan Hayadi; Cindy Paramitha; Muhammad Sadikin (JUDIMAS, 2020)
The Internet of Things (IoT) is a fast growing and user-friendly technology that connects everything together. And it can communicate effectively between the people who connect "Things." Internet of Things, also known as Internet of Objects, usually refers to remote systems between projects. Systems will be remote and self-designable. However, the world's largest information technology companies tend to release products in the form of services to avoid disclosing detailed design and implementation knowledge. Hence, the overall trend of academic institutions is to use these mainstream IoT platforms as "black boxes". IoT is something that is useful as a sensor, computer architecture, software, security, packaging, technology selection based on the amount of data, as far as data is needed, whatever power you have. Fundamental way to collect and store data Thing: SQL, noSQL, and time series databases Machine learning algorithms with outputs: regression, classification, anomaly detection. Improve service quality, reduce service costs New models (precision services), Reduce consumption costs of higher quality products or services, Improve health and safety.